2016
DOI: 10.3847/0067-0049/224/2/22
|View full text |Cite
|
Sign up to set email alerts
|

The Young Stellar Population of Lynds 1340. An Infrared View

Abstract: We present results of an infrared study of the molecular cloud Lynds 1340, forming three groups of low-and intermediate-mass stars. Our goals are to identify and characterize the young stellar population of the cloud, study the relationships between the properties of the cloud and the emergent stellar groups, and integrate L1340 into the picture of the star-forming activity of our Galactic environment. We selected candidate young stellar objects (YSOs) from the Spitzer and WISE databases using various publishe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 56 publications
(95 reference statements)
1
35
0
Order By: Relevance
“…After inspection of the large scale structure of the outflow and of the WISE 3.4µm, 4.6µm, 12µm, & 22µm images we conclude that the source of the flow is not in the region suggested by Kumar et al (2002), but that it lies 1.6-1.8 to the southeast along the flow axis and that the flow is driven by either SSTSL2 J022820.81+723500.5 or SSTSL2 J022818.51+723506.2. We prefer this as the source region (similar to the conclusion of Kun et al 2016b) instead of that suggested by Kumar et al (2002) because these two candidate source stars were both classified as Class 0/I by Kun et al (2016b) and SSTSL2 J022820.81+723500.5 was discussed as a candidate Class 0 source. In addition, the filamentary H 2 structure around these two sources (MHO 2928 G) passes through the sources themselves and could plausibly be a jet, unlike the filament (MHO 2928 B) south of the Kumar et al (2002) source star.…”
Section: A Bright Curved Outflow: Mho 2928 Hh 488 B Hh 488 Cmentioning
confidence: 91%
See 3 more Smart Citations
“…After inspection of the large scale structure of the outflow and of the WISE 3.4µm, 4.6µm, 12µm, & 22µm images we conclude that the source of the flow is not in the region suggested by Kumar et al (2002), but that it lies 1.6-1.8 to the southeast along the flow axis and that the flow is driven by either SSTSL2 J022820.81+723500.5 or SSTSL2 J022818.51+723506.2. We prefer this as the source region (similar to the conclusion of Kun et al 2016b) instead of that suggested by Kumar et al (2002) because these two candidate source stars were both classified as Class 0/I by Kun et al (2016b) and SSTSL2 J022820.81+723500.5 was discussed as a candidate Class 0 source. In addition, the filamentary H 2 structure around these two sources (MHO 2928 G) passes through the sources themselves and could plausibly be a jet, unlike the filament (MHO 2928 B) south of the Kumar et al (2002) source star.…”
Section: A Bright Curved Outflow: Mho 2928 Hh 488 B Hh 488 Cmentioning
confidence: 91%
“…Kumar et al (2002) suggested that the flow was launched from a star which corresponds to SSTSL2 J022759.92+723556.4, a probable double star. Kun et al (2016b) catalog it as a flat SED source, but note that the SED "results from the composite fluxes of the central objects". This region is very complex and Kumar et al (2002) identified two candidate jets in Hα and [Sii] emerging from two stars (which they designated S1 and S2) separated by about 2 arcseconds at position angles of 320 and 275 degrees respectively.…”
Section: A Bright Curved Outflow: Mho 2928 Hh 488 B Hh 488 Cmentioning
confidence: 99%
See 2 more Smart Citations
“…7 of Luhman et al 2009). The number of Class II YSOs are also similar in both star-forming regions (Luhman et al 2010;Kun et al 2016), whereas they are different in volume, molecular mass and kinetic temperature, structure, and Galactic environment (Kenyon, Gómez, & Whitney 2008). To check whether disk properties observed in the two apparently coeval star-forming regions can be distinguished or not, we collected statistical data in Table 8.…”
Section: The Optically Selected Yso Population Of L1340mentioning
confidence: 99%